German philosophy in English translation - Hawkins, Spencer, author.
1 online resource.
Keywords: This book traces the translation history of twentieth-century German philosophy into English, with significant layovers in Paris, and proposes an innovative approach to long-standing difficulties in its translation. German philosophy's reputation for profundity is often understood to lie in German's polysemous vocabulary, which is notoriously difficult to translate even into its close relative, English. Hawkins shows the merit in a strategy of differential translation, which involves translating conceptually dense German terms with multiple different terms in the target text, rather than the conventional standard of selecting one term in English for consistent translation. German Philosophy in English Translation explores how debates around this strategy have polarized both the French-language and English-language translation landscapes. Well-known translators and commissioners such as Jean Beaufret, Adam Phillips, and Joan Stambaugh come out boldly in favor, and others such as Jean Laplanche and Terry Pinkard polemically against it. Drawing on Hans Blumenberg's work on metaphor, German Philosophy in English Translation questions prevalent norms around the translation of terminology that obscure the metaphoric dimension of German philosophical vocabulary. This book is a crucial reference for translators and researchers interested in the German language, and particularly for scholars in translation studies, philosophy, and intellectual history.